Analysis of Guidance and Counseling Programs in High School - Rike Wulandari; Firman; Neviyarni S (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The guidance and counseling service program is an integrated part of the overall educational program at school. Therefore, the efforts of supervising teachers and the various aspects covered by the program are an inseparable part of all activities directed towards achieving educational goals at the institution concerned. To achieve this maturity, students need help because they still lack understanding or insight about themselves and their environment as well as experience in determining the direction of their lives. This research uses a literature review method where researchers conduct a series of research involving various kinds of information originating from literature such as books, documents, Google Scholar and so on. As a result of this research, this program aims to facilitate students in getting to know themselves and their environment positively, making responsible decisions, as well as developing their potential and achieving their developmental tasks. The BK program is structured based on student needs assessment, school needs, community demands, and student development tasks. The BK program in high school consists of various types of programs such as annual, semester, monthly, weekly and daily programs. The preparation of the guidance and counseling program is based on student needs assessment, taking into account four areas of guidance (personal, social, learning, career) as well as types of supporting services and activities.